Le trésor d’une nomade. Luise Straus-Ernst : le récit de vie d’une Allemande réfugiée en France - Mechthild Gilzmer (Diasporas: Circulations, Migrations, Histoire)
This article analyses the life story of Luise Straus-Ernst, an art historian and first wife of the artist Max Ernst, who was born in Cologne in 1893 and perished in Auschwitz in 1944. She wrote The Treasures of a Nomad in Manosque where she had found refuge thanks to the author, Jean Giono. The retrospective text reflects an awakening as well as the profound reflection of an extraordinary woman confronted with an extreme situation. The text allows us to reconstitutes the different stages of her life and exile in France, and to analyse how she regarded her own past and exile as a woman.